Imaginaries of resistance: the Andean ecofeminist rap of Taki Amaru and Renata Flores - Pinilla-Alba, Susana (2024)
In a reality marked by humanitarian and climate crises, there is an urgent need to review the pillars of a worldview that justifies and entrenches the catastrophe, by seeking solutions to counteract its effects. With this purpose, this article presents and analyzes some representative works of the Peruvian Renata Flores and the Colombian MC Taki Amaru, from La Mafiandina. From a critical ecofeminist perspective, the article examines how some concepts (sumak kawsay, body-territory and ch'ixi) dialogue and contribute to feminist philosophy. Through an analysis of the rappers’s aesthetics (the representations of women and nature), their ethics (the vindication of a dignified life) and their political posture (the defense of one's own body), it reveals the critical and didactic potential of Latin American ecofeminism and the multiple possibilities of rap as a tool for social change, environmental pedagogy and empowerment of oppressed groups.